A case study of patriarchy and slavery: the hermeneutical importance of Qurʾānic assumptions in the development of a values-based and purposive oriented Qurʾān-sunna hermeneutic - Duderija, A. (2013)
It is the task of this paper to argue that the development of a new Qurʾān-sunna hermeneutic(and therefore Islamic legal theory) which hermeneutically privileges an ethico-religious and purposive approach to a Qurʾānic interpretation (based on ethically objectivist nature of ethical value) has the potential to engender a gender symmetrical Islamic law. In order for this to be achieved, it is argued further, that the hermeneutical importance of the mirroring of the various socio-cultural and ethico-moral assumptions prevalent in the Qurʾān’s revelatory milieu in the actual Qurʾānic text itself must be taken into account as evident in those passages pertaining to the patriarchal nature of socio-legal aspects of gender dynamics and existence of slavery, especially female concubinage. Additionally, in the first part of the paper, I briefly discuss one reason why I consider the classical Islamic scholarship failed to explore the hermeneutical significance of these assumptions and therefore did not engender a Qurʾānic hermeneutic and Islamic legal theory that hermeneutically privileges an ethicoreligious and purposive based approach to interpretation of Qurʾān and sunna. I refer to this process as a hermeneutical shift from a Qurʾān-sunna interpretive dialogical approach to that of a sunna-ḥadith episteme.